Privatization, competition for deposits and performance in banking - Ruiz Porras, Antonio (Estudios de Economía, 2016)
In this article we develop a microeconomic framework to study the relationships among privatization, competition for deposits and performance in banking. Particularly, we analyze banking privatization when competitive strategies of the Cournot and Stackelberg types are allowed. Our findings show that some conditions are necessary to justify it under the following criteria: (i) efficiency, (ii) market power/financial stability and (iii) consumption availability for depositors. They also show that privatizations are relatively easy to justify when leader-follower relationships are allowed in the banking system. Even government revenues, due to privatization, are higher when these relationships exist.